Role of serum fibroblast growth factor-23 and Klotho level in COVID-19 infection-related mortality: a prospective study - Akin, Davut; Aydogan, Burcu B; Emre, Nilufer; Gundogdu, Gulsah; Ozmen, Sehmus; Erkek, Ozgen K; Alpua, Mehmet (The Journal of Infection in Developing Countries, 2024)
Introduction: This study investigated the role of fibroblast growth factor 23 (FGF23)/Klotho in the mortality of patients hospitalized with coronavirus disease 2019 (COVID-19), excluding those with chronic kidney disease (CKD). Methodology: A prospective cross-sectional study was conducted from April 2021 to May 2022. Patients who tested positive for COVID-19 via polymerase chain reaction and were hospitalized, were classified into two groups (survivors and non-survivors) at the end of their hospital follow-up. Demographic data, clinical status, and prognosis were analyzed. Results: A total of 66 patients (age 58.8 ± 17.0 years, 60.6% male) were included. The mean age of non-survivors (67.2 ± 1 years) was significantly higher than the survivors (49.2 ± 1 years; p < 0.0001). FGF23 was significantly elevated in non-survivors (301 ± 20 pg/mL), compared to survivors (160 ± 36 pg/mL; p < 0.0001). Factors with significant differences (p < 0.001) between the two groups were investigated as independent mortality predictors using logistic regression analysis. FGF23 (p = 0.01), age (p = 0.045), and oxygen saturation at admission (p = 0.02) were independent predictors of mortality. High serum FGF23 levels were associated with COVID-19-related mortality; Klotho levels were lower (p = 0.028). Vitamin D was not significantly different between the groups. Conclusion: Elevated serum FGF23 and parathyroid hormone (PTH), and lower Klotho levels, were associated with COVID-19-related mortality in patients without CKD. There was no association with serum vitamin D levels. Further studies are required to establish the relationship between mortality and FGF23/Klotho, PTH, and vitamin D levels.